Covid-19 Pandemic and Persons with Disabilities: Impacts and Risk Factors, Lessons for Future Interventions - Muhammed Yahya (International Journal of Coronaviruses, 2022)
Background The pandemic has disrupted the lives of many globally including persons with disabilities. These disruptions are universal. However, the vulnerable communities are more affected. Purpose The study examines impacts on persons with disabilities to share knowledge and inform interventions that ensure persons with disabilities are supported. Methodology The study is a systematic literature review using different search engines to search for scholarly articles all over the globe. Results Persons with disabilities have been negatively impacted in numerous ways: lack of access to healthcare services, inadequate rehabilitation services, increased human rights violation, stigmatization and discrimination, increased risk of dying, being subjected to violence, losing financial income, lack of access to education and treatment, increased in neglect and traumatization, poverty, lack of access to food, decreased in community support; and worse of all, in comparison with the overall population, the death of persons with disabilities during the Covid-19 is higher. These impacts were precipitated by inaccessible built environment and sense of touching, lack of disability sensitive policies, increased prevalence of risk factors, difficulties in adhering to WHO recommendations, pervasiveness of underlying health conditions, lack of disability-friendly information and inclusive intervention, national budget cuts; and poorly funded institutions. Conclusion Persons with disabilities have been negatively impacted due to many risk factors peculiar to them.
Keywords: Persons with disabilities